2018
DOI: 10.1029/2018jc013987
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Stratification and Low Melt Rates at the Ross Ice Shelf Grounding Zone

Abstract: Ocean-driven melting of ice shelves is a primary mechanism for ice loss from Antarctica.However, due to the difficulty in accessing the sub-ice shelf ocean cavity, the relationship between ice shelf melting and ocean conditions is poorly understood, particularly near the grounding zone, where the ice transitions from grounded to floating. We present the first borehole oceanographic observations from the grounding zone of the Ross Ice Shelf, Antarctica's largest ice shelf by area. Contrary to predictions that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 80 publications
8
87
1
Order By: Relevance
“…The drag coefficient, C d , is a key parameter in the three‐equation parameterization of ice shelf basal melting and is used to relate the free stream velocity beyond the turbulent boundary to the friction velocity at the ice shelf‐ocean interface through a quadratic drag law (Jenkins et al, ). C d is poorly constrained by observations, however, and is often used to tune models to match observed melt rates (e.g., Begeman et al, ; Dutrieux et al, ). In reality, the drag coefficient is likely to be highly spatially and temporally variable (Gwyther et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drag coefficient, C d , is a key parameter in the three‐equation parameterization of ice shelf basal melting and is used to relate the free stream velocity beyond the turbulent boundary to the friction velocity at the ice shelf‐ocean interface through a quadratic drag law (Jenkins et al, ). C d is poorly constrained by observations, however, and is often used to tune models to match observed melt rates (e.g., Begeman et al, ; Dutrieux et al, ). In reality, the drag coefficient is likely to be highly spatially and temporally variable (Gwyther et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Current parameterizations of basal melting, however, are poorly constrained by observations, and different parameterizations can yield model melt rates that vary by up to a factor of 5 (Dansereau et al, 2014). The canonical three-equation melt rate parameterization (Holland & Jenkins, 1999) has only been calibrated for a single location (Jenkins et al, 2010) and often requires regional tuning to match observed melt rates (Begeman et al, 2018;Dutrieux et al, 2014). Furthermore, the three-equation parameterization is known to perform poorly when predicting the melt rate in the presence of strong stratification (Kimura et al, 2015) or a buoyancy-driven plume flowing along a sloped ice shelf base (McConnochie & Kerr, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This site is within the grounding zone as determined by the limits of ice flexure from differential synthetic aperture radar interferometry (Marsh et al, ). The ice shelf thickness at the site was 757 ± 1 m, and the ocean cavity was 10 m thick (Begeman et al, ). We deployed a sensor string containing a pressure sensor and 30 thermistors on 16 January 2015.…”
Section: Methodsmentioning
confidence: 99%
“…We deployed a sensor string containing a pressure sensor and 30 thermistors on 16 January 2015. The pressure sensor hung 761 m from the ice surface, roughly middepth in the ocean cavity, within a water mass of almost constant potential density (Begeman et al, ). The thermistors were distributed throughout the ice shelf with a maximum spacing of 100 m and a minimum spacing of 1 m near the ice shelf bottom.…”
Section: Methodsmentioning
confidence: 99%
“…The GZ site was 4.8 km downstream from the physical grounding line of the WIS (Figure 1). The ice cover at the GZ was~760 m thick, and the underlying marine water column was~10 m deep (Begeman et al, 2018;Christianson et al, 2016).…”
Section: Site Descriptionmentioning
confidence: 99%